One size fits all? Decentralization, corruption, and the monitoring of bureaucrats - Christian Lessmann; Gunther Markwardt (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2008)
The majority of theoretical and empirical studies on the relationship between decentralization and corruption argues that the devolution of power might be a feasible instrument to keep corruption at bay. We argue that this result crucially depends on the possibility to monitor bureaucrat's behavior. The benefits of interjurisdictional competition only occur if there is a supervisory body such as a free press, which is often lacking in less-developed countries. Using crosscountry data, we analyze the relationship between decentralization and corruption taking different degrees of the freedom of the press into account. Our main finding is that decentralization counteracts corruption in countries with high degrees of press freedom, whereas countries with low monitoring possibilities suffer from decentralization. Our policy implication is, therefore, that a free press is a necessary pre-condition for successful decentralization programs.
Keywords: D73; H72; H77; 330; decentralization; corruption; freedom of press; Gewaltenteilung; Dezentralisierung; Korruption; Meinungsfreiheit; Bürokratie; Schätzung; Welt